High-performance work systems and job engagement: The mediating role of psychological empowerment - Md. Shamsul Arefin (Taylor & Francis Group, 2019)
Drawing on the social exchange theory, this study aimed to investigate the mediating role of psychological empowerment in the relationship between high-performance work systems and job engagement. Data collected from 287 employees in a large manufacturing organization was analyzed using structural equation modeling and hierarchical regression analysis. The results showed that perceived high-performance work systems and psychological empowerment positively influenced job engagement. The results of the study also revealed that psychological empowerment mediated the influence of high-performance work systems on job engagement. The results further suggest that organizational human resources systems impact job engagement through psychological empowerment. The theoretical contribution and managerial implications have been thoroughly discussed in this paper.